Penjadwalan Berbasis MAC 802.11 dan Routing ACO padaWireless Sensor Network - RA Fattah Adriansyah; Reza Firsandaya Malik (Ikatan Ahli Informatika Indonesia (IAII), 2019)
Wireless Sensor Network (WSN) has limited energy characteristics so that the proper configuration is needed in order to create the WSN has a low energy consumption to extend the WSN’s life time. By utilizing the collision incident which is difficult to avoid while nodes transmit data packets so that it can reduce the network’s performance, and then makes it as an active - sleep scheduling that can improve the energy efficiency of WSN. So in this study, we proposed an Ant Colony Optimization (ACO) based routing protocol with collision based MAC 802.11 which will be compared with ACO based routing protocol with MAC 802.11 on WSN in terms of energy efficiency. The results obtained from the simulation carried out is that WSN on the grid topology with the small number of nodes (12 nodes) that using an ACO routing protocol with MAC 802.11 collision based has increased energy efficiency by 91.7% while with the large number of nodes (70 nodes) has increased energy efficiency by 81.4%.